The impact of the European Accounting Review on accounting research (1992-2019) - Martínez-García, Aitor; Horrach-Rosselló, Patricia; Valluzzi, Chiara; Mulet-Forteza, Carles (De Computis, Revista Española de Historia de la Contabilidad., 2021)
This paper analyzes the contribution that the European Accounting Review has made to accounting research since it was launched in 1992. Among the many motives for writing this paper, we believe that the most important ones are to identify the evolution of the main areas of research and to predict future trends in the field of accounting. Via a bibliometric approach, we have analyzed a total of 952 European Accounting Review publications indexed in the Scopus database since its inception, as well as 22,605 publications from 18 other journals indexed in the first quartile in the subject category ’accounting’ of the Scopus database. We have identified the most influential documents and authors based on their publications and citations, the most productive institutions and their co-citation patterns, and the most prolific countries over three sub periods: 1992-2000, 2001- 2010 and 2011-2019. We have also examined past and current research topics giving special attention to ‘accounting history’ to study the significance of this field of research in the journal. Some of our findings show that the most productive authors in EAR are Christopher Humphrey, David Alexander, Christopher W. Nobes, Pat Sucher and Begoña Giner. Regarding institutions and countries, the British, Spanish, and Dutch excelled in productivity. The topic ‘disclosure’ was the most addressed from 1992 to 2010, whereas ‘audit’ and ‘IFRS’ took the lead in the last decade. We have also studied the journal’s patterns of publication on ‘accounting history’. Our findings reveal that, although the publications in that field have been decreasing over the years, 9% of all documents published in the EAR are in that field of research.